PELAKSANAAN GANTI KERUGIAN PEMBANGUNAN JALAN TOL PADANG–SICINCIN (STUDI KASUS: KANTOR KEMENTERIAN AGRARIA DAN TATA RUANG/BADAN PERTANAHAN NASIONAL (ATR/BPN) KABUPATEN PADANG PARIAMAN) - Sembiring, Susanti; Zuleika, Siti Fatimah (Ensiklopedia of Journal, 2026)
Abstract: One of the most important stages in land acquisition for development in the public interest is the compensation mechanism. Within this mechanism, there is a stage known as deliberation for the determination of compensation. In many land acquisition cases, the deliberation process often fails to reach an agreement. This condition is caused by objections and refusals from rights holders regarding the amount or value of compensation determined by the government. This study describes the actual conditions of land acquisition implementation in Padang Pariaman Regency at the location of the Padang–Sicincin Toll Road Project. It explains the role of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Office as the technical implementer, the stages of land acquisition, and the compensation valuation process conducted by the Independent Appraisal Team.  The main findings indicate that the compensation value is widely rejected by the community because it is considered too low and does not include non-physical losses. The deliberation mechanism is also perceived as less participatory, thereby triggering conflicts. Nominative data, appraisal results, and field studies serve as concrete evidence of these issues. Based on the research results, this study analyzes the discrepancy between theory and practice in the implementation of compensation for toll road projects. The research identifies that the compensation mechanism has not fully reflected the principles of justice, transparency, and deliberation as regulated in the prevailing laws and regulations. Factors such as the dominant governmental approach, limited community participation, and the exclusion of non-physical compensation are identified as the main causes of conflict. This analysis is strengthened by interview findings and comparisons with positive law provisions.  Keywords: Compensation, Toll Road, Padang, Sicincin.Boedi Harsono, Hukum Agraria Indonesia: Sejarah Pembentukan Undang-Undang Pokok Agraria, Jakarta: Djambatan, 2008Boedi Harsono, Hukum Agraria Indonesia: Sejarah Pembentukan Undang-Undang Pokok Agraria, Djambatan, Jakarta, 2005Erna Dwi Lestari, Implementasi Kebijakan Pengadaan Tanah untuk Kepentingan Umum, Rajawali Press, Jakarta, 2015D. Santoso, Prinsip-Prinsip Pengadaan Tanah untuk Pembangunan Kepentingan Umum, Gramedia Pustaka Utama, Jakarta, 2020DalamPetunjuk Teknis SPI306,Komite PenyusunStandarPenilaianIndonesiadan Masyarakat PenilaiIndonesia (MAPPI),2015.John Rawls, A Theory of Justice, Harvard University Press, 1971Kementrian Pekerjaan Umum dan Perumahan Rakyat, Jaringan Jalan Tol Trans Sumatera, Kementerian PUPR, 2023.Kusumaatmadja, Pengantar Hukum Pembangunan, Bandung: Alumni, 2002Konsorsium Pembaruan Agraria, 2017. Reformasi Agraria di Bawah Bayangan Investasi, Catatan Akhir Tahun 2017M. Kusumawati, Analisis Konflik Pengadaan Tanah dalam Pembangunan Jalan Tol di Indonesia, Jurnal Hukum & Pembangunan, vol. 7, no. 1 2021Maria S.W. Sumardjono, Tanah dalam Perspektif Hak Ekonomi, Sosial, dan Budaya, Jakarta: Kompas, 2009Maria Sumardjono, Kebijakan Pertanahan Antara Regulasi dan Implementasi Gadjah Mada University Press, Yogyakarta, 2009Muchsin, Pendaftaran Tanah dan Sertifikasi Hak Atas Tanah, Citra Aditya Bakti, Bandung, 2012R. Wirawan, Aspek Sosial dalam Pengadaan Tanah untuk Infrastruktur di Indonesia, Yogyakarta: Pustaka Pelajar, 2019Sudikno Mertokusumo, Hukum Acara Perdata Indonesia, Yogyakarta: Liberty, 2010Satjipto Rahardjo, Hukum dalam Jagat Ketertiban, Genta Publishing, Yogyakarta, 2006, hlmSiti Sundari Rangkuti, Hukum Agraria dan Hak-Hak Atas Tanah, Rajawali Press, Jakarta, 2018John W Brush, Reforming Land Law to Acieve Development Goals on Land Law Reform, The International Bank for Reconstruction and Development/World Bank Washington D, 2006.